The Deactivation of Implantable Cardioverter-Defibrillators: Medical, Ethical, Practical, and Legal Considerations - Carlsson, Jörg (Deutscher Arzte Verlag, 2012)
BACKGROUND: Implantable cardioverter-defibrillators (ICDs) cannot prevent death from progressive heart failure or non-cardiac disease. Patients with ICDs may receive defibrillation therapy from their devices in the last days of their lives, when such therapy does not accord with the goal of palliative treatment, but rather lowers these patients’ quality of life and compromises their dignity. METHODS: We present a case report and a selective review of pertinent literature retrieved by a PubMed search, including two up-to-date consensus documents. RESULTS: One-third to two-thirds of all ICD patients receive defibrillation therapy in the final days of their lives. Patients and their physicians rarely discuss deactivating the ICD. The ethical aspects of such decisions need to be considered. As a practical matter, it is possible to deactivate certain types of electrotherapy selectively, while leaving others active. There are logistical considerations as well. CONCLUSION: Automatic defibrillation therapy in a terminally ill patient with an ICD is painful and distressing, serves no medical purpose, and should be avoided. This issue should be discussed with ICD patients and their families. Institutions caring for terminally ill patients, as well as cardiology units where ICD patients are treated, should develop ethically and legally well-founded protocols for dealing with the question of ICD deactivation.